2003
DOI: 10.1037/0735-7036.117.4.414
|View full text |Cite
|
Sign up to set email alerts
|

Imitation and Affordance Learning by Pigeons (Columba livia).

Abstract: The bidirectional control procedure was used to determine whether pigeons (Columba livia) would imitate a demonstrator that pushed a sliding screen for food. One group of observers saw a trained demonstrator push a sliding screen door with its beak (imitation group), whereas 2 other groups watched the screen move independently (possibly learning how the environment works) with a conspecific either present (affordance learning with social facilitation) or absent (affordance learning alone). A 4th group could no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 13 publications
2
87
0
1
Order By: Relevance
“…It is possible that the observation of a demonstrator moving the treadle with a distinctive part of its body is more detectable than the observation of it moving the screen in a distinctive direction. However, earlier research with this same apparatus found that pigeons demonstrated significant matching of left-right screen pushing (Klein & Zentall, 2003). In fact, in that study, pigeons tended to match the direction of their demonstrator's screen push (85.0%) to the same extent as pigeons in a previous study tended to match their demonstrator's treadle response (84.2%; Dorrance & Zentall, 2001).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…It is possible that the observation of a demonstrator moving the treadle with a distinctive part of its body is more detectable than the observation of it moving the screen in a distinctive direction. However, earlier research with this same apparatus found that pigeons demonstrated significant matching of left-right screen pushing (Klein & Zentall, 2003). In fact, in that study, pigeons tended to match the direction of their demonstrator's screen push (85.0%) to the same extent as pigeons in a previous study tended to match their demonstrator's treadle response (84.2%; Dorrance & Zentall, 2001).…”
Section: Discussionmentioning
confidence: 52%
“…When tested, the observer quail showed a significant tendency to push the screen in the same direction as their demonstrator. Furthermore, when control observers saw the screen move without being pushed by the demonstrator (a control for object-movement reenactment or learned affordances), they did not match the direction of screen movement (see also Klein & Zentall, 2003, for inclusion of a control for possible odor cues). Thus, the bidirectional control procedure appears to provide a valid alternative procedure for demonstrating imitation in birds.…”
mentioning
confidence: 99%
“…When observation of a demonstrator allows an animal to learn how the environment functions, a sophisticated form of learning may be involved. For example, if a pigeon observes a screen (that is capable of moving to the left or to the right) move to the left to allow access to food, when the pigeon is given access to the screen, it is more likely to move the screen in the same direction (Campbell, Heyes, & Goldsmith, 1999;Klein & Zentall, 2003). However, because learning how the environment works may occur in the absence of the behavior of another animal, one would not want to view such learning as social learning.…”
Section: Goal Emulation Object-movement Reenactment and Emulation Vmentioning
confidence: 99%
“…Learning about things and how they work by observation has important implications for cognitive learning. There is evidence not only that chimpanzees can emulate the movement of a tool (Nagell, Olguin, & Tomasello, 1993), as well as increasing the level of water in a cylinder to gain access to a reward (Tennie et al, 2010), but also that pigeons (Klein & Zentall, 2003) and dogs (Miller, Rayburn-Reeves, & Zentall, 2009) can emulate the direction of movement of a screen permitting access to food.…”
Section: Goal Emulation Object-movement Reenactment and Emulation Vmentioning
confidence: 99%
See 1 more Smart Citation